Thirty years of entrepreneurship research published in top journals: analysis of citations, co-citations and themes - Manuel Portugal Ferreira; Nuno R. Reis; Rui Miranda (Journal of Global Entrepreneurship Research, 2015)
Entrepreneurship research has increased markedly over the past three decades. In this paper we conduct a large scale survey of the literature beyond a subjective perspective on what entrepreneurship research has comprised. We investigate what have been the intellectual structure and the knowledge base underlying published entrepreneurship research. Moreover, we also conduct a longitudinal analysis of the main research themes that have caught scholars' efforts. Using bibliometric techniques on a sample of 1,777 articles published in 17 top ranked journals, between 1981 and 2010, we conduct analyses of citations, co-citations and co-occurrences to examine the most central works, themes and how they intertwine. Results provide evidence of the increasing interest in entrepreneurship as a field of study, but also of its interdisciplinary nature, with infusions of concepts and theories from a wide array of management disciplines. This paper provides a brief but extensive rear view of the field useful for both doctoral students and newcomers to the discipline develop their own research agendas.
Keywords: 650; Bibliometric study; Entrepreneurship field; Literature review; Research trends